Tragedi dalam Harmoni: Budaya, Gender, dan Kekerasan pada Perempuan di Jawa Barat - Yulianingsih Yulianingsih; Erna Herawati (Universitas Andalas, 2022)
People in West Java uphold harmony and peace as an important part of their worldview. Yet, violence against women continues to occur, including in rural areas. This qualitative research using a case study design was conducted to explore and describe the cases of violence against women and the factors contributing to the case in Desa Selaras, a small village in rural West Java. The data were collected through observation and in-depth interviews with female violence survivors and NGO activists who assist them; as well as archival and literature studies. The findings of this research suggest the various types of violence against women, such as psychological violence (polygamy), physical violence (persecution), economic violence (economic exploitation and financial neglect), and sexual violence. Among the factors contributing to the violence in the village were gender inequality, financial problems, lack of knowledge and passive attitudes towards violence among the survivors, cultural values about women, lack of communication in the family, and male personality.